The development of cooperative learning models of Make A Macth type of historical materials of the formulation and rativication of the 1945 Constitution to improve of students’ learning outcomes - Mashuri, Defa (International Journal for Educational and Vocational Studies, 2021)
This study was conducted in the 2018/2019 academic year and is motivated by the learning outcomes of class VII students for the 2017/2018 academic year on the historical material of the formulation and ratification of the 1945 NRI Constitution which has not yet reached the KKM: 75.00 with an average grade per grade of 55.00. The objectives of this study are 1). Produce validity, practicality, and effect liveness of the learning model Pkn. This type of research is the research and development of a 4-D model design with modifications to 3-D adapted from Thiagarajan. Limited trials were conducted in class VII-A. Data collection techniques used validation, observation, questionnaires, pre-test & post-test ins trumpets. The study data analysis yielded:1). The validity level of the syllabus is: 3.17, RPP: 3.28, Bas: 3.17, Lks: 3.19, Question Card: 3.12 & Answer Card: 3.27 and Assessment Card: 3.19 and Pre-test questions: 3.22 & Post-test questions: 3.19.2). The level of practicality of the average Rpp implementation: 3.34, Average Bas readability: 89.63%, and Lks: 90.85%. 3). The level of effectiveness of student responses showed positive responses with an average: 86.60% of the learning tools. Students' activities when teaching and learning process in class showed 86.60% of VII-A students were very active in following the make a match learning model. Analysis of learning outcomes obtained an average N-Gain: 0.58 and showed an increase with the average category average and pre-test average value: 60.09 & post-test average value: 83.61.